Analisis Yuridis Implementasi Platform LAPOR TBC dalam Mendukung Eliminasi Tuberkulosis di Indonesia - Erin Kusumawati; Fajar Rachmad Dwi Miarsa; Deby Ayu Wulandari (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Tuberculosis (TB) is one of the major health problems in Indonesia, with high rates of spread and social stigma that worsens the condition of survivors. The LAPOR TB platform is present as a digital innovation to support TB elimination through increased access to justice and the fulfillment of health rights. This study analyzes the implementation of the LAPOR TB platform from a juridical perspective, using normative research methods that involve legislative and conceptual approaches. The results of the study show that this platform has great potential to improve access to health services for TB survivors, but still faces various legal challenges, including personal data protection, limited access to technology, ineffective complaint mechanisms, and weak law enforcement. Therefore, it is necessary to strengthen legal policies, improve technological infrastructure, and eliminate social stigma to ensure that this platform can run effectively. With these steps, LAPOR TB is expected to be able to support TB elimination efforts and fulfill the right to health for all Indonesian people.